Analisis Pengukuran Kinerja Keuangan PT Bank Negara Indonesia (PERSERO) TBK Dengan Metode Economic Value Added (EVA) Periode 2022-2024 - Septia Khoirina; Dhuha Safria; Chanissa Purwaningrum (CV. ITTC INDONESIA, 2025)
This study aims to analyse the measurement of financial performance using the Economic Value Added (EVA) method for the period 2022-2024. The research was conducted at PT Bank Negara Indonesia (Persero) Tbk as the object under study. The population and sample are the company's last 3 (three) years of financial statements. The research method uses quantitative methods through a descriptive approach. The sampling technique used is the saturated sample technique. The data analysis technique uses formulas in accordance with the Economic Value Added (EVA) method and uses some of the company's financial statement data as the required analysis material. The results showed that the financial performance of PT Bank Negara Indonesia (Persero) Tbk, for the period 2022-2024 was still considered positive but still low. PT Bank Negara Indonesia (Persero) Tbk, in the period 2022-2024, has not been able to create economic value added in the morning of its shareholders. Judging from the results of the calculation of Economic Value Added (EVA) shows a negative value, which means ‘Does Not Have Economic Added Value’. PT Bank Negara Indonesia (Persero) Tbk, in the period 2022-2024, is still considered ‘Negative’. Judging from the results of the calculation of Economic Value Added (EVA) which shows the value of Net Operating Profit After Tax (NOPAT) is smaller than the value of Capital Charger (Capital Cost).